PARTICIPATORY DEVELOPMENT PLANNING IN SUMBANG VILLAGE, CURIO DISTRICT, ENREKANG REGENCY - Rukmana, Novayanti Sopia; Hanafi Gani, Imran; Sakawati, Herlina; Purna, Zarni Adia (Jurnal Aktor, 2024)
The level of community participation in the implementation of development planning deliberations at the Sumbang Village level is quite high, because the community begins to be active in the implementation of Musrenbang by attending the implementation of Musrenbang and proposing opinions and suggestions regarding the work program that will be implemented for one year; and Factors that affect the level of community participation in the Development Planning Deliberations at the Sumbang Village level include:  Factors to the community's activity in participating in participation, factors for the activeness of village governments, factors for the availability of resources, be it in the form of funds, human resources, or infrastructure facilities in Musrenbang in Sumbang Village, Curio District, Enrekang Regency.